A new model of bi-component droplet heating and evaporation; Physics of Fluids; Vol. 37 - Antonov D. V. Dmitry Vladimirovich; Tonini S. Simona; Cossali G. Gianpietro; Sazhin S. S. Sergey Stepanovich (2025, 2025)
Title screen